(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes the didactic potential of CLIL (Content and Language Integrated Learning), one of the modern pedagogical technologies used in teaching English. The study examines the integration of language and subject content through the CLIL methodology, the development of students’ communicative competence, the promotion of interdisciplinary integration, and the formation of independent thinking skills among learners. The research also explores the theoretical foundations of the CLIL approach, its role and effectiveness in the teaching process, as well as its didactic opportunities in English language education from a scientific perspective.